Learning from action : management of Aboriginal and Torres Strait Islander Health Services - Dwyer, Judith, 1951-; Shannon, Cindy; Godwin, Shirley; Cooperative Research Centre for Aboriginal Health (Australia); Queensland Aboriginal and Islander Health Council; La Trobe University; Flinders University; Cooperative Research Centres Program (Australia) (Casuarina, N.T. : Cooperative Research Centre for Aboriginal Health, 2007)
49 page document published 2007. This project used an action learning and research approach to develop understanding of management practices in Aboriginal Health Services; to share and build knowledge and skills; and to develop a research agenda.
"August 2007".
"CRC Australia"--T.p. verso.
Bibliography: p. 43-45.
Also available in an electronic format via the Internet. Address as at 5 March 2008: http://www.crcah.org.au/publications
Funded by the Cooperative Research Centre for Aboriginal Health, La Trobe University and Flinders University in partnership with the Queensland Aboriginal and Islander Health Council.
Keywords: Aboriginal Australians -- Health and hygiene; Torres Strait Islanders -- Health and hygiene; Health services administration -- Australia; Health planning -- Australia; Health services - Management; Health services - Health workers; Health services - Community health centres; Health - Policy and administration; Australia